Implications of Training Pathways on Future Academic Plastic Surgeon Employment. Issue 6 (December 2020) - Glener, Adam D.; Glener, Steven R.; Shammas, Ronnie L.; Le, Elliot; Cason, Roger W.; Rezak, Kristen; Phillips, Brett T.
Abstract : Background: The limited supply of academic plastic surgery positions has led to increased demand and strong competition for these desired positions. Residents and students now seek out academic opportunities earlier in their training to account for this employment shortage. Training pathways and locations play an extremely important role in obtaining an academic position at most institutions. This study aimed to evaluate the training patterns of academic plastic surgeons in an attempt to elucidate its value and role for trainees interested in pursuing future academic careers. Methods: All full-time faculty members at currently accredited integrated and independent plastic surgery programs were included in the study; clinical affiliates were excluded. These institutions' websites were then queried to obtain the training history of the surgeons meeting inclusion criteria. Data were entered into a centralized database from which descriptive statistics were obtained. Results: In the 741 surgeons included in the study, 514 (69.4%) completed the independent plastic surgery track and 227 (30.6%) completed the integrated pathway. Residents completing the independent track had 20.8% and 31.7% employment at the same institution where they finished their general and plastic surgery residency, respectively. Of those completing the integrated pathway, 33.9% are employed at the same institution where they graduated from residency. In addition, 47.9% of the surgeons included in the study completed medical school, residency, or fellowship at the current institution at which they are employed. Lastly, 512 surgeons (69.4%) completed at least 1 postresidency fellowship. Conclusions: Academic surgeons commonly complete a postresidency fellowship and are often employed at institutions where they have formerly trained. Trainees considering an academic career should consider these patterns when planning their future careers.